Entropy generation metric for evaluating and forecasting aircraft energy management systems. (2nd May 2005) - Hallinan, Kevin P.; Sanders, Brian; Somphone, Thada; Ephrem, George
A general Entropy Generation Minimisation (EGM) technique is applied to analyse the feasibility of energy recovery from aircraft avionics via thermoelectric (TE) devices. In employing this approach, a suitable control volume definition is chosen to evaluate the impact of an energy recovery system on the overall entropy generation of the aircraft over a mission. Only those systems which are affected by the energy harvesting system are considered. As importantly, the analysis helps to identify the technical thresholds, which must be realised in order to make avionic energy harvesting via thermoelectric devices practical. This result has exciting implications for the use of this tool for helping to prioritise research directions. Relative to the energy harvesting application from the radar array on a high efficiency aircraft, the results from this approach show that a majority of the entropy generation and fuel exergy wastage is associated with the avionics cooling system due the transfer of heat to the cooling system and to the large mass/power ratio associated with cooling systems.